AeU brand lures retiree to pursue PhD - New, Straits Times (New Straits Times, 2014)
Learning is lifelong process for retiree - PhD/Doctoral degree is deemed as most prestigious for a life time - Stephanie Ng, PhD in Business Administration, Asia e University (AeU)